Schiff bases in medicinal chemistry: a patent review (2010-2015). (2nd January 2017) - Hameed, Abdul; al-Rashida, Mariya; Uroos, Maliha; Abid Ali, Syed; Khan, Khalid Mohammed
ABSTRACT: Introduction : Schiff bases are synthetically accessible and structurally diverse compounds, typically obtained by facile condensation between an aldehyde, or a ketone with primary amines. Schiff bases contain an azomethine (-C = N-) linkage that stitches together two or more biologically active aromatic/heterocyclic scaffolds to form various molecular hybrids with interesting biological properties. Schiff bases are versatile metal complexing agents and have been known to coordinate all metals to form stable metal complexes with vast therapeutic applications. Areas covered : This review aims to provide a comprehensive overview of the various patented therapeutic applications of Schiff bases and their metal complexes from 2010 to 2015. Expert opinion : Schiff bases are a popular class of compounds with interesting biological properties. Schiff bases are also versatile metal complexing ligands and have been used to coordinate almost all d-block metals as well as lanthanides. Therapeutically, Schiff bases and their metal complexes have been reported to exhibit a wide range of biological activities such as antibacterial including antimycobacterial, antifungal, antiviral, antimalarial, antiinflammatory, antioxidant, pesticidal, cytotoxic, enzyme inhibitory, and anticancer including DNA damage.